Studi Komparatif Pidana Pengawasan dalam Sistem Peradilan Pidana Indonesia dan Belanda - Ainun Majid, Muhammad Zulfitrah; Usman, Usman; Imam Munandar, Tri (PAMPAS: Journal of Criminal Law, 2026)
This study aims to identify and analyze the types of acts or crimes that can be subject to criminal supervision sanctions in Indonesia and the Netherlands, as well as to provide a comprehensive understanding of the application of criminal supervision sanctions in the Indonesian and Dutch criminal law systems, so that it can be used as input for the development of national criminal law. The type of research used is normative juridical research, using legislative approach methods, comparative approaches, and conceptual approaches. The results of this study indicate that in Indonesia, the new Criminal Code stipulates criminal supervision sanctions for defendants with a maximum sentence of 5 years in prison, and a supervision period of no more than 3 years. Meanwhile, in the Netherlands, it is regulated in the Wetboek van Strafrecht for defendants who are threatened with a sentence of more than 2 years, a maximum of 4 years with a probationary period of 3 years and a maximum of 10 years, and in Indonesia the implementation is carried out by the Judicial Institution, the Prosecutor's Office, and the Correctional Institution. Meanwhile, in the Netherlands, supervision is carried out in a more structured manner by the Reclassering Institution together with the Public Prosecutor based on the Wetboek van Strafvordering, so the system is more systematic than in Indonesia. It is hoped that Indonesia will establish a special institution for criminal supervision to be more structured and systematic, and will immediately ratify the Criminal Code. ABSTRAK Penelitian ini bertujuan, untuk mengetahui dan menganalisis jenis-jenis perbuatan atau tindak pidana yang dapat dikenakan sanksi Pidana Pengawasan di Indonesia dan Belanda, dan untuk memberikan pemahaman yang komprehensif mengenai penerapan pidana pengawasan dalam sistem hukum pidana Indonesia dan Belanda, sehingga dapat menjadi bahan masukan bagi pengembangan hukum pidana nasional. Jenis penelitian yang digunakan yaitu penelitian yuridis normatif, dengan menggunakan metode pendekatan perundang-undangan, pendekatan komparatif dan pendekatan konseptual. Hasil dari penelitian ini menunjukan bahwa di Indonesia, Kitab Undang-Undang Hukum Pidana baru menetapkan pidana pengawasan bagi Terdakwa dengan ancaman hukuman paling lama 5 tahun penjara, dan pidana pengawasannya tidak lebih dari 3 tahun. Sedangkan di Belanda, diatur dalam Wetboek van Strafrecht bagi Terdakwa yang diancam dengan pidana lebih dari 2 tahun maksimal 4 tahun dengan masa percobaan 3 tahun dan paling lama 10 tahun, dan di Indonesia pelaksanaannya dilakukan oleh Lembaga Peradilan, Kejaksaan, dan Badan Pemasyarakatan. Sementara di Belanda, pengawasan dijalankan secara lebih terstruktur oleh Lembaga Reclassering bersama Jaksa berdasarkan Wetboek van Strafvordering, sehingga sistemnya lebih sistematis dibanding di Indonesia. Diharapkan di Indonesia membentuk lembaga khusus untuk pidana pengawasan agar lebih terstruktur dan sistematis, dan segera mengesahkan Kitab Undang-Undang Hukum Acara Pidana